Pengaktifan UKGS Sekolah Dasar Pesisir Dalam Memberikan Edukasi Trend Estetik Gigi Terhadap Dampak Oral Hygiene Masyarakat Teluk Kadere Kelurahan Bontang Lestari Kota Bontang Kalimantan Timur - Astuti, Lilies Anggarwati; Pramasari, Nadya C.; Irsal, Imran; Masyhudi, Masyhudi; Alus, Levi Natya (Jurnal BALIRESO, 2023)
Specific objectives to be achieved are giving birth to independent young dentists who are aware of the importance of maintaining oral and dental health in the form of UKGS program activation. In Bontang East Borneo, in particular, public awareness of the importance of dental and oral health still needs to be improved. On this basis, we want to try to offer a product development of human resources (HR) in the field of dentistry. The method used in the form of training for young dentists and young doctors, training, and assistance to students in primary school and teachers, mass toothbrushing practices, dental and oral examinations and procedures, and reactivation of the UKGS program by completing facilities that have not been there. Target and outcome which are expected: 1) Producing a cadre of young dentists and young doctors, 2) Increase knowledge in all students in primary school related to maintaining dental and oral dental, 3) Creating awareness of dental and oral dental which is reflected in healthy living behavior and 4) reactivate the UKGS program.